Language breakdown in primary progressive aphasias - Amitabha Ghosh (Annals of Indian Academy of Neurology, 2020)
Dementias with predominant language involvement, called primary progressive aphasias provide us with unique insight into systematic breakdown of language in neurodegenerative diseases and the structures and networks involved. Clinical and neuroimaging models quite distinct from those seen in stroke aphasias have evolved. In this short overview, we will discuss the cognitive processes involved in expressive and receptive verbal communication and how these processes are affected in the different variants of primary progressive aphasia producing distinctive clinical patterns. We will also discuss the brain's language network and how different components of the network break down in each of the primary progressive aphasia variants.